Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) VI: new descriptions of Ocellarnaca Gorochov, 2004 - Lu, Xiangyi; Zhang, Qianwen; Bian, Xun (Zootaxa, 2022)
In this paper, we report one new species, viz. Ocellarnaca longilobulata sp. nov. (Chinese name: 长叶眼斑蟋螽), and provide the descriptions of tegminal veins and morphological illustrations of Ocellarnaca fuscotessellata (Karny, 1926) (Chinese name: 锈褐眼斑螽) and Ocellarnaca furcifera (Karny, 1926) (Chinese name: 叉眼斑蟋螽). All the specimens are deposited in Guangxi Normal University.